The Effect of Technology of Acceptance Model on the Gojek 4.0 Application on Repurchase Intention - Ditha Damayanti (Jurnal Mantik, 2021)
One of the technologies that is being widely developed in Indonesia is online applications. The presence of online applications has an impact on people's daily activities. Gojek is one of the largest technology platforms serving millions of users in Southeast Asia. Referring to the theory of technology acceptance model (TAM), and this study examines other antecedents: perceived enjoyment, perceived innovativeness, perceived risk, perceived easy of use, and perceived usefulness as predictors of satisfaction. Furthermore, the role of satisfaction in increasing the intention of repurchase, and reducing price sensitivity. Eight hypotheses were analyzed with structural equations of modeling approaches, using 349 respondents collected by purposive sampling. The results show that unless perceived easy of use and perceived innovativeness, all antecedents can drive satisfaction. Furthermore, satisfaction affects direct, and indirect price sensitivity through repurchase intention.